ANALISIS PERILAKU KONSUMEN PRODUK SYNGENTA: KASUS DI KECAMATAN KETAHUN KABUPATEN BENGKULU UTARA - Priyono, Basuki Sigit; Arianti, Nyayu Neti; H. Siahaan, Tumbur Masco (Jurnal AGRISEP, 2010)
The purposes of this research are to determine the factors related to consumer perception on Syngenta products; to analyse relation between farmer perceptionon Syngenta product and purchasing behavior; and to examine the most product used by consumer.The research is done intentionally to 96 respondents. Two method analyses use in this study, i.e., a descriptive analysis and Rank Kendall correlation (t). The study finds that family income and farmer views significantly correlate to the consumer perception on Syngenta products, whereas the farm area and farmer experience are not. This study also concludes that consumer perception Syngenta product is not related tothe purchasing behavior. According to respondents,they often use herbicide of gramoxone.